2019
DOI: 10.5194/acp-2019-133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of biogenically-derived aerosols over the Amundsen Sea, Antarctica

Abstract: <p><strong>Abstract.</strong> To investigate the influence of marine biological activity on aerosols, aerosol and seawater samples were collected over the Southern Ocean (43° S−70° S) and the Amundsen Sea (70° S−75° S) during the ANA06B cruise conducted in the austral summer of 2016 aboard the Korean icebreaker IBR/V <i>A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Based on airmass trajectories, they attributed the high particle concentrations to lofting of biogenic gases by the polar circulation to the free troposphere over Antarctica, new particle formation there, with subsequent descent back to the MBL related to cyclonic activity. The formation of new, ultrafine particles also has been observed directly in the summertime marine boundary layer in the Antarctic coastal zone where biological activity is enhanced (Jokinen et al, 2018;Jung et al, 2019;Yu & Gan, 2010). The Webb et al (2019) study found that DMS fluxes (Pandis et al, 1994) were sufficient 63% of the time to produce new H 2 SO 4 CCN under MBL conditions on the West Antarctic Peninsula.…”
Section: Sources Of Cloud Condensation Nucleimentioning
confidence: 93%
“…Based on airmass trajectories, they attributed the high particle concentrations to lofting of biogenic gases by the polar circulation to the free troposphere over Antarctica, new particle formation there, with subsequent descent back to the MBL related to cyclonic activity. The formation of new, ultrafine particles also has been observed directly in the summertime marine boundary layer in the Antarctic coastal zone where biological activity is enhanced (Jokinen et al, 2018;Jung et al, 2019;Yu & Gan, 2010). The Webb et al (2019) study found that DMS fluxes (Pandis et al, 1994) were sufficient 63% of the time to produce new H 2 SO 4 CCN under MBL conditions on the West Antarctic Peninsula.…”
Section: Sources Of Cloud Condensation Nucleimentioning
confidence: 93%
“…Air mass back trajectories were calculated using the HYS-PLIT4 (Hybrid Single Particle Lagrangian Integrated Trajectory) trajectory model (Draxler and Hess, 1998) using the NCAR/NCEP (National Centers for Atmospheric Prediction/National Center for Atmospheric Research) 2.5 • global reanalysis archive (Kalnay et al, 1996). Trajectories were calculated arriving at Halley (75 • 34 16 S, 25 • 28 26 W; 30 m above sea level -a.s.l.)…”
Section: Air Mass Trajectoriesmentioning
confidence: 99%
“…In addition, sulfur-containing compounds in the class of carbohydrates and proteins have been recently identified in HULIS extracts of aerosols collected in the coastal area of South Korea [54]. Moreover, protein-like components were found dominant in marine aerosols sampled over the Amundsen Sea as a result of biological activity [55]. Similar compounds are shown to be electroactive on Hg [56][57][58].…”
Section: Electrochemical Rss Responses In Ws Fraction Of Fine Marine mentioning
confidence: 99%